2007
DOI: 10.1002/srin.200706297
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Formation of Open‐Eye and Slag Entrainment in Gas Stirred Ladle

Abstract: Laboratory experiments were carried out to study the phenomena related to open‐eye formation in ladle treatment. Ga‐In‐Sn alloy with a melting temperature of 283 K was used to simulate the liquid steel, while MgCI2‐Glycerol(87%) solution as well as HCl solution were used to simulate the ladle slag. No open‐eye was formed at lower gas flow rates, but, occurred when gas flow reached a critical rate. This critical gas flow rate was found to depend significantly on the height of the top liquid. No noticeable amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…In contrast, the viscosity of the top liquid and interfacial tension between the two liquids has only a slight effect on the open‐eye size. Similar work has been by Thuman et al where they used Ga–In–Sn alloy with a melting temperature of 283 K (10 °C) to simulate the liquid steel and an MGCL 2 ‐Glycerol (87%) solution to simulate the slag. It was found that no open‐eye formed at lower flow rates, but did occur when the gas flow reached a critical rate.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, the viscosity of the top liquid and interfacial tension between the two liquids has only a slight effect on the open‐eye size. Similar work has been by Thuman et al where they used Ga–In–Sn alloy with a melting temperature of 283 K (10 °C) to simulate the liquid steel and an MGCL 2 ‐Glycerol (87%) solution to simulate the slag. It was found that no open‐eye formed at lower flow rates, but did occur when the gas flow reached a critical rate.…”
Section: Introductionmentioning
confidence: 82%
“…Studies related to studying the open‐eye in a gas‐stirred ladle through physical modeling and numerical simulation have been performed extensively in the past three decades. Yonezawa and Schwerdtfeger carried out cold model measurements using mercury and silicone oil to represent liquid metal and slag, respectively, for investigating the open‐eye size in the ladle.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few works about physical models of the ladle furnace that considered the three phase system gas-steel-slag [3][4][5][6]. These works evaluate several issues, being one of the most important to quantify how much is the mixing time increased by the presence of the slag layer.…”
Section: Introductionmentioning
confidence: 98%
“…However, a bare metal surface region, called the "open-eye", will be observable when the velocity of argon bubbles is large enough and the slag layer is relatively thin. The open-eye region increases the amount of oxygen dissolvable in molten steel, therefore resulting in re-oxidation and slag entrapment [8,9]. In addition, the heat loss will escalate due to the argon gas having a comparatively lower temperature than the molten steel.…”
Section: Introductionmentioning
confidence: 99%